Law and social norms - Posner, Eric A., 1965- (Harvard University Press, 2000)
"What is the role of law in a society in which order is maintained mostly through social norms, trust, and nonlegal sanctions? Eric Posner argues that social norms are sometimes desirable yet sometimes odious, and that the law is critical to enhancing good social norms and undermining bad ones. But he also argues that the proper regulation of such norms is a delicate and complex task, and that current understanding of them is inadequate for guiding judges and lawmakers. What is needed, and what this book offers, is a model of the relationship between law and social norms. The model shows that people's concern with establishing cooperative relationships leads them to engage in certain kinds of imitative behavior. The resulting behavioral patterns are called social norms."--Jacket